2017
DOI: 10.1093/sleep/zsx157
|View full text |Cite|
|
Sign up to set email alerts
|

CPAP Does Not Reduce Inflammatory Biomarkers in Patients With Coronary Artery Disease and Nonsleepy Obstructive Sleep Apnea: A Randomized Controlled Trial

Abstract: ClinicalTrials.gov, ID: NCT00519597; researchweb.org, VGSKAS-4731.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 31 publications
4
21
0
3
Order By: Relevance
“…24 Previously conducted cross-sectional, casecontrol, prospective cohort studies as well as randomized controlled trials provided evidence for a positive association between sleep behaviors and inflammatory mediators such as CRP, IL-6, IL-8, TNF-, and von Willebrand factor antigen. 20,32,35,37,40,41,47 However, these studies were heterogeneous with respect to target population as well as definition of sleep behavior, with the majority focused on OSA. We found that hours of sleep were not related to WBC markers, after controlling for sociodemographics, lifestyle, and health characteristics, including periodontitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Previously conducted cross-sectional, casecontrol, prospective cohort studies as well as randomized controlled trials provided evidence for a positive association between sleep behaviors and inflammatory mediators such as CRP, IL-6, IL-8, TNF-, and von Willebrand factor antigen. 20,32,35,37,40,41,47 However, these studies were heterogeneous with respect to target population as well as definition of sleep behavior, with the majority focused on OSA. We found that hours of sleep were not related to WBC markers, after controlling for sociodemographics, lifestyle, and health characteristics, including periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…A priori confounders for the hypothesized relationships were identified based on the existing literature 16,20,25,26,28,29,[31][32][33][34][35][36][37][38][39][40][41] and classified as sociodemographic, lifestyle, and healthrelated characteristics. Sociodemographic characteristics included age (in years; 30 to 34, 35 to 39, 40 to 44, 45 to 49, 50 to 54, 55 to 59, 60 to 64, 65 to 96, and ≥70), race (Mexican American, other Hispanic, non-Hispanic white, non-Hispanic black, and other), education (<high school, 9th to 11th grade, high school graduate/GED or equivalent, some college or AA degree, college graduate or higher), marital status (married/living with partner, other) and poverty income ratio (<100%, 100% to <200%, and ≥200%).…”
Section: Covariatesmentioning
confidence: 99%
“…The pooling of eight published reports in adults with OSAS revealed that plasma IL-6 levels ranged from 1.2 to 131.7 pg/mL before CPAP treatment and signi cantly decreased to between 0.45 to 66.04 pg/mL after CPAP treatment [48]. However, among those studies, there was signi cant inter-individual heterogeneity [9] which may be related to the variance for IL-6 genes, environmental and/or lifestyle in uences [49,50]. Potential interactions between OSAS, obesity, and both genetic, environmental, and lifestyle factors, ultimately lead to a cascade of pathophysiological pathways, resulting in increased systemic in ammation, as illustrated by increased levels of IL-6 [9,50].…”
Section: Discussionmentioning
confidence: 99%
“…THUNSTRÖM et al [102] analysed the RICCADSA data regarding levels of high-sensitivity C-reactive protein, interleukin (IL)-6, IL-8 and tumour necrosis factor-α. The biomarkers were measured at baseline and after 1 year of follow-up in 220 patients randomised to CPAP or no CPAP.…”
Section: Treatment Effectmentioning
confidence: 99%